ANALISIS STRUKTUR DAN KOMUNITAS LAMUN SEBAGAI HABITAT PENYU DI PANTAI KAHYAPU KECAMATAN ENGGANO PROVINSI BENGKULU - DEWI PURNAMA (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2013)
This study is a preliminary research about.seagrass as an important shallow marine biota at Desa Kahyapu Beach, Enggano, North Bengkulu. This research used survey method. The study revealed that seagrass reticence at Kahyapu seashore about 80-95%. There are only two species of seagrass were found in this region: Enhalus accoroides and Cymodocea sp. The density of Enhalus accoroides in three observation sites ranging from 655 to797.5m2, while Cymodocea sp ranging from 388 to 471/m2. Physics and chemistry analysis show that Kahyapushore have a good criteria for growth and development of aquatic organism including seagrass. The average of aquatic temperature, velocity, clarity, acidity and dissolved oxygen consecutively are 32°C, 0.72m/dt, 100%, 34.3 ppm, and 7.4 mg/l. Organic suspension in sediment ranging from 15.6 to 22.7 mg/I and the solid particle suspension about 13.9 -22 mg/l.